New application of dydrogesterone as a part of a progestin-primed ovarian stimulation protocol for IVF: a randomized controlled trial including 516 first IVF/ICSI cycles. Issue 2 (29th December 2017) - Yu, Sha; Long, Hui; Chang, Hannah Ya-ning; Liu, Yali; Gao, Hongyuan; Zhu, Jing; Quan, Xinxin; Lyu, Qifeng; Kuang, Yanping; Ai, Ai
Abstract: STUDY QUESTION: Can dydrogesterone (DYG) be used as an alternative progestin in a progesterone primed ovarian stimulation (PPOS) protocol? SUMMARY ANSWER: DYG can be used as an appropriate alternative progestin in a PPOS protocol. WHAT IS KNOWN ALREADY: PPOS is a new ovarian stimulation regimen based on a freeze-all strategy that uses progestin as an alternative to a GnRH analog for suppressing a premature LH surge during the follicular phase. Medroxyprogesterone acetate (MPA) has been successfully used as an adjuvant to gonadotrophin in the PPOS protocol. However, the use of MPA may lead to stronger pituitary suppression and thus may require a higher dosage of hMG and a longer duration of ovarian stimulation than that of conventional ovarian stimulation protocol. STUDY DESIGN SIZE, DURATION: A prospective RCT including 516 patients was performed between November 2015 and November 2016. Computerized randomization was conducted to assign participants at a 1:1 ratio into two treatment groups: an hMG + DYG group (260 patients) or an hMG + MPA group (256 patients) followed by IVF or ICSI with the freeze-all strategy. One cycle per patient was included. The primary outcome of the trial was the number of oocytes retrieved. The sample size was chosen to detect a difference of two oocytes with a power of 90%. PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients under 36 years of age with normal ovarian reserve who were undergoing their first IVF/ICSI procedure due to tubal factor infertility were randomized into two groups based on the oral progestin protocol used: hMG co-treatment with DYG (hMG + DYG) or hMG co-treatment with MPA (hMG + MPA). The different progestin was simultaneously administered at the beginning of menstrual cycle 3 (MC3). Oocyte maturation was co-triggered by administration of a GnRH agonist and hCG. All viable embryos from both protocols were cryopreserved for later transfer. Only the first frozen embryo transfer (FET) cycle was included in our study. The embryological and clinical outcomes were measured. MAIN RESULTS AND THE ROLE OF CHANCE: Basic characteristics, such as age, BMI and infertility duration, in both groups were comparable. There was no significant difference in the number (mean ± SD) of oocytes retrieved [10.8 ± 6.3 for the hMG + DYG group versus 11.1 ± 5.8 for the hMG + MPA group, P = 0.33] or the oocyte retrieval rate [74.3 ± 19.6% for the hMG + DYG group versus 75.0 ± 19.5% for the hMG + MPA group, P = 0.69] between the groups. The viable embryo rate per oocyte retrieved did not differ between the two groups [odds ratio (OR): 1.08, 95% CI: 0.97–1.21, P = 0.16]: 37.4% (1052/2815) for the hMG + DYG group versus 35.6% (1009/2837) for the hMG + MPA group. During the whole process of ovarian stimulation, the mean LH level in the hMG + DYG group was always higher than that in the hMG + MPA group ( P < 0.001); however, no patient from either group experienced a premature LH surge. In addition, no patients experienced moderate or severe ovarian hyperstimulation syndrome during the ovarian stimulation. No significant difference was found in the clinical pregnancy rate of the first FET cycle between the two groups (OR: 0.82, 95% CI: 0.56–1.21, P = 0.33): 57.6% for the hMG + DYG group (125/217) versus 62.3% for the hMG + MPA group (132/212). LIMITATIONS REASONS FOR CAUTION: The patients and physician were not blinded to the study. Further, a large proportion of patients were still pregnant at the end of the clinical trial, therefore live birth rates were not observed in the follow-up period. The dose-effectiveness of DYG administration was not addressed in the trial design. WIDER IMPLICATIONS OF THE FINDINGS: DYG, which exhibits no or only weak inhibition of ovulation in normal dosage, can serve as an hMG adjuvant during ovarian stimulation. This finding suggests the possibility of a new application of DYG: as an appropriate alternative progestin for a PPOS protocol in IVF. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by The National Nature Science Foundation of China (Grant no. 81503603), Shanghai Three-year Plan on Promoting TCM Development (Grant no. ZY3-LCPT-2-2006) and the Natural Science Foundation of Shanghai (Grant nos. 15401932700 and 15ZR1424900). None of the authors declare any conflict of interest. TRIAL REGISTRATION NUMBER: Chictr.org.cn: ChiCTR-IPR-15007251. TRIAL REGISTRATION DATE: Chictr.org.cn: 22 October 2015. DATE OF FIRST PATIENT'S ENROLLMENT: 1 November 2015.